INVESTMENT SUPPORT FOR THE INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISES - HUANG, Bingru (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the investment aspects of promoting the innovative development of agricultural enterprises. The purpose of this study is to analyze current trends, challenges, and prospects for investing in Ukraine’s agricultural sector, and to provide substantiated directions for enhancing investment support to drive the industry’s innovative development. To achieve this goal, the study examines the current state of investment in Ukraine’s agricultural sector, considering its role in ensuring food security, promoting economic growth, and fostering the development of related industries. The dynamics of capital investment from 2021 to 2023 are examined by enterprise size and area of agricultural production. The importance of attracting capital investment for production modernization, enhancing competitiveness, and adapting agricultural enterprises to crisis conditions is substantiated. The distribution of investments in tangible and intangible assets is examined, encompassing machinery and equipment, the construction and reconstruction of production facilities, the acquisition of software, and intellectual property. It was found that, following a significant decline in investment due to military actions and a deterioration in the investment climate, 2023 witnessed a recovery, indicating the gradual adaptation of enterprises to new conditions. The analysis of capital investment distribution by enterprise size revealed that medium and large farms account for the largest share of investments. At the same time, small and micro-enterprises focus on less capital-intensive areas. In sectoral terms, investments are primarily driven by crop production and livestock farming, reflecting the strategic importance of these subsectors. Further strengthening of the agricultural sector’s investment potential requires: the formation of a stable and predictable macroeconomic and regulatory environment; expanded access to financing, particularly through public-private partnerships, tax incentives, and foreign direct investment; stimulation of innovation and digitalization of production; intensification of state and international support, including grant funding and the development of agricultural innovation infrastructure; and support for investments in "green" and resource-saving technologies. The implementation of these measures will help create a sustainable investment ecosystem, boost innovative activity, and enhance the agricultural sector’s resilience to internal and external challenges.